Desain Produk Minyak Angin Aromaterapi Sweet Care Hasil Ekstraksi Kayu Manis (Cinnamomum burmanii) - Anitarakhmi Handaratri; Siswi Astuti; Ayudya Mahendaringratry (G-Tech: Jurnal Teknologi Terapan, 2023)
Cinnamon is often used as an active ingredient by the pharmaceutical industry, as a fragrance by the cosmetic industry, by direct application to food, or it can also be incorporated into food packaging. To produce aromatherapy oil from cinnamon, the process is simply use the Mixing and filter method. The purpose of this research is to design a manufacturing process for aromatherapy/fresh care oils whose ingredients are natural ingredients that can be found in Indonesia (indigenous natural resources). The research method used is Research and Design (RnD). Perceptual mapping analysis shows that this product can compete with aromatherapy wind oil products on the market. The planned production capacity is 19,656 tons per year.